THE INFLUENCE OF FIZULI IN THE LITERARY ENVIRONMENT OF KOKON: TRADITION AND RENEWAL (TAMADDUN NURI JURNALI, 2025)
In this article written a comprehensive analysis of the importance of literary influence in the Kokand literary environment of the second half of the 19th and early 20th centuries. In particular, the influence of Fuzuli’s work on Muhyi and his contemporary poets is revealed in detail. It is considered on the basis of specific examples that poets such as Hazari, Muqimi and Muhyi find a distinctive reflection of the Fuzuli style in ghazal and mukhammas. At the same time, the place and value of this literary influence in Uzbek poetry in aesthetic and spiritual terms is illuminated. The article also focuses on how the Fuzuli tradition is perceived in the Kokand literary environment, their influence on the lyric of love in Uzbek classical poetry, and the individual style of poets in the process. As a result, deep traces of Fuzuli’s work in Uzbek literature are highlighted.